2019
DOI: 10.1038/s41467-019-08729-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autophagic activity by Rubicon is a signature of aging

Abstract: Autophagy, an evolutionarily conserved cytoplasmic degradation system, has been implicated as a convergent mechanism in various longevity pathways. Autophagic activity decreases with age in several organisms, but the underlying mechanism is unclear. Here, we show that the expression of Rubicon, a negative regulator of autophagy, increases in aged worm, fly and mouse tissues at transcript and/or protein levels, suggesting that an age-dependent increase in Rubicon impairs autophagy over time, and thereby curtail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
147
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 52 publications
(54 reference statements)
12
147
1
Order By: Relevance
“…Rubicon, along with Bcl-2 15 , is one of most prominent negative regulators of autophagy and is therefore considered a promising target for autophagy inducing therapeutics 11,12 . Despite its significance, however, the only available structural data have been a 6 Å cryo-EM and hydrogen-deuterium exchange characterization of a short portion of the central IDR as bound to PI3KC3-C2 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubicon, along with Bcl-2 15 , is one of most prominent negative regulators of autophagy and is therefore considered a promising target for autophagy inducing therapeutics 11,12 . Despite its significance, however, the only available structural data have been a 6 Å cryo-EM and hydrogen-deuterium exchange characterization of a short portion of the central IDR as bound to PI3KC3-C2 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Rubicon is targeted to its sites of action by the late endosomal small GTPase Rab7 9,10 . Autophagy suppression by Rubicon in aging has been linked to decreased clearance of α-synuclein aggregates in neural tissues, impairment of liver cell homeostasis, and interstitial fibrosis in the kidney [11][12][13] . Together with another target for autophagy inducing therapeutics, Bcl-2 14,15 , Rubicon is one of very few known broadly-acting negative regulators of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Current efforts are dedicated to understanding the biological process of aging and to identify pathways that can be targeted to extend health and life spans. Interestingly, it has been demonstrated that many of the pathways that improve health and extend longevity in various organisms all converge on autophagy (1)(2)(3)(4)(5)(6)(7)(8). Autophagy is a catabolic pathway that is responsible for recycling cellular proteins and organelles to maintain energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a key pathway in cellular quality control by eliminating dysfunctional or unwanted organelles and protein aggregates. However, there is strong evidence that autophagy is decreased with age in tissues, including the heart (5,(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of phage-derived anti-CRISPR proteins 4-6 , i.e. potent inhibitors of Cas effectors, provides a shut-off mechanism that can keep this powerful technology in check 7 and enhance the precision at which genome perturbations can be made [8][9][10][11] . While mining of sequence databases and screening of phage libraries proved to be powerful strategies to discover Acrs targeting a variety of Cas effectors 5, 6, 12-18 , these approaches are inherently limited to the naturally occurring protein sequence space.…”
mentioning
confidence: 99%